Documento de arquivo: uma análise sobre as legislações arquivísticas para documentos nato-digitais - SOUZA, Ingrid Pacheco de (2022)
The analysis of Federal and state laws and the academic production of Archival Science about digital and born-digital documents aims to identify the symmetries and asymmetries between research and legislation, seeking specifically to highlight the similarities and differences between the documents that are in digital media, in addition to its characteristics, preservation and security of information, considering that the laws for digital and born-digital documents, must be in agreement with what is already established by the academic community. The methodology was divided into two parts, starting with surveying academic research on the subject of digital and born-digital documents and then addressing the identification of current legislation on digital and born-digital documents. The universe of the research was delimited in relation to the federal and state legislation favorable to the archival science context and the scientific communications about the academic conceptualization of borndigital documents, besides the search in the Google Scholar knowledge bases. The discussion is divided into two sections, one that refers to the Federal Legislation and another that deals with the Pará State Legislation, where issues and crucial points that were highlighted during this research are mentioned and were mentioned in the theoretical assumptions and their sections. The final considerations deal with the whole theme of the Brazilian Federal and State Legislation that does not really discuss or have as their main theme the born-digital documents or documents in digital media, and treat them equally. Finally, it is proposed to evaluate all Brazilian Federal and State Legislation that discusses the theme, so that a manual is made based on the weaknesses that occur in those that already exist.